On the meaning of life in relation to good company - Guendel Angulo, Hermann (2025)
In this essay the author explores the possibility of finding the deep meaning of life in the bond of intimacy with others, which allows, over the time, to constitute the intense experience of the joy that good company provides. The author defends this by proposing the interpretation of the human person as a community subject. That requires coexistence to those that he recognizes as his equals in order to transcend the physical and symbolic limitations of the routine existence.